Understanding adherence-related beliefs about medicine amongst patients of South Asian origin with diabetes and cardiovascular disease patients: a qualitative synthesis. Issue 1 (December 2016) - Kumar, Kanta; Greenfield, Sheila; Raza, Karim; Gill, Paramjit; Stack, Rebecca
Abstract Background Prevalence of diabetes and cardiovascular (CVD) disease amongst UK South Asians is higher than in the general population. Non-adherence to medicines may lead to poor clinical outcomes for South Asian patients with diabetes and CVD. To understand the decision making processes associated with taking medicines, a qualitative systematic meta-synthesis exploring medicine taking behaviours, and beliefs was undertaken. Methods Four databases (Medline, Embase, Science Citation Index and CINAHL) were searched to identify qualitative studies of South Asian patients taking diabetic medicines. Data were thematic coded and synthesised. Results The following themes were identified: [1] beliefs about the need for and efficacy of medicines; [2] toxicity of medicines and polypharmacy; [3] the necessity of traditional remedies versus "western medicines"; [4] stigma and social support; and [5] communication. Conclusions South Asians described cultural social stigma associated with diabetes and reported fears about drug toxicity as barriers to taking medicines. Cultural beliefs about traditional remedies and interactions with healthcare professionals also appeared to play a role in the way people made decisions about medicines. Advice should be tailored provided to South Asian patients highlighting the long term consequences of diabetes and CVD.